Pharmacokinetics, Safety and Tolerability of Rotigotine Transdermal Patch in Healthy Japanese and Caucasian Subjects - Cawello, Willi (Springer International Publishing, 2013)
BACKGROUND AND OBJECTIVES: Rotigotine is a dopamine receptor agonist with activity across the D(1) through to D(5) receptors as well as select serotonergic and adrenergic sites; continuous transdermal delivery of rotigotine with replacement of the patch once daily maintains stable plasma concentrations over 24 h. Rotigotine is indicated for the treatment of early and advanced-stage Parkinson’s disease and moderate-to-severe idiopathic restless legs syndrome. The pharmacokinetics and pharmacodynamics of a drug may vary between subjects of different ethnic origin. This study evaluated the pharmacokinetics, safety, and tolerability of single-dose treatment with rotigotine transdermal patch in Japanese and Caucasian subjects. METHODS: In this open-label, parallel-group study, healthy male and female subjects of Japanese or Caucasian ethnic origin were matched by sex, body mass index, and age. A single transdermal patch delivering 2 mg/24 h rotigotine (patch content 4.5 mg) was applied to the ventral/lateral abdomen for 24 h. The main outcome measures were the plasma concentrations of unconjugated and total rotigotine and its desalkyl metabolites and derived pharmacokinetic parameters (area under the concentration–time curve from time zero to last quantifiable concentration [AUC(last)], maximum plasma concentration [C (max)], and body weight- and dose-normalized values). RESULTS: The pharmacokinetic analysis included 48 subjects (24 Japanese, 24 Caucasian). The mean apparent dose of rotigotine was 2.0 ± 0.5 mg for Japanese subjects and 2.08 ± 0.58 mg for Caucasians. Plasma concentration–time profiles of unconjugated rotigotine and of the main metabolites were similar for both ethnic groups. Parameters of model-independent pharmacokinetics, C (max), time to C (max) (t (max)), and AUC(last), for unconjugated rotigotine showed no statistically significant differences between Japanese and Caucasian subjects. Values of concentration-dependent pharmacokinetic parameters were higher in female subjects; this difference was minimized after correction for body weight. A statistically significant difference between ethnic groups was observed for total rotigotine concentrations (total rotigotine = unconjugated rotigotine + conjugated rotigotine), with slightly lower values in Caucasians after correction for body weight and apparent dose. No relevant differences were observed between males and females. Inter-individual variability was high. The terminal half-life for unconjugated rotigotine was 5.3 h in Japanese subjects and 5.7 h in Caucasians; corresponding values for total rotigotine were 8.6 h and 9.6 h. Less than 0.1 % of the apparent dose was renally excreted as the parent compound. Renal elimination of total rotigotine covers 11.7 % of absorbed dose in Japanese subjects and 10.8 % of the absorbed dose in Caucasians, whereas the renal elimination via total despropyl rotigotine was 8.2 and 7.1 %, respectively. The corresponding values for total desthienylethyl rotigotine were 3.5 % in Japanese subjects and 4.2 % Caucasians. Most adverse events were mild in intensity and typical for dopamine agonists or for transdermal therapeutics. CONCLUSION: Administration of a single patch delivering 2 mg/24 h rotigotine resulted in comparable pharmacokinetic profiles in Japanese and Caucasian subjects. The rotigotine transdermal patch was generally well-tolerated. Our findings suggest similar dose requirements for Japanese and Caucasian populations.